Keeping Identity, Freedom, and Independence of Polish Exiles in Siberia in 19th Century (till 1914). Part I - Caban, Wiesław (Respectus Philologicus, 2015)
First Poles were sent to Siberia to an exile as early as the second half of the 18th century to be followed by the participants of the Napoleonic campaign of 1812. It is estimated that after the fall of the November Uprising (1831), about ten thousand young Poles were taken captive and deported to Siberia. Soon they were joined by those, especially from Lithuania and Belarus, who were engaged in a conspiracy. More than twenty thousand people were exiled to Siberia after the fall of the January Uprising (1863); whereas, the beginning of 1880s saw the deportation in large numbers of those who were members of socialist parties. The majority of deportees had the opinion that the time in exile should be devoted to self-education and self-organization. The necessity to cultivate patriotic sentiments and Catholic religion was unquestionable. They tried to create at least a semblance of homeland to some degree in exile. Among a certain group of deportees there was a strong conviction that it is not enough to cultivate or even strengthen Polish traditions to get ready for the economic development of Poland, once the independence is regained. It was not enough to conspire, it was necessary to take immediate steps such as escape or rebellion that would bring freedom. One of the best known cases of such thinking is the so called Omsk Conspiracy. In 1833, the deportees from the Omsk region, counting on the support of the local Siberian community, came up with a plan for an uprising. Another revolt against stardom was planned in 1866 in Transbaikal. Both of those attempts failed.
Keywords: 19th Century; Poles; Siberia; Exile